First Cytogenetic and Karyomorphological Analysis of Two Endemic Plant Species, Arbutus pavarii and Origanum cyrenaicum, from Al-Jabal Al-Akhdar, Libya - Jamila Bashasha; Yousif Imryed; Halima Adam (AlQalam Journal of Medical and Applied Sciences, 2026)
This study provides the first cytogenetic and karyomorphological analysis of two endemic Libyan plant species, Arbutus pavarii (Ericaceae) and Origanum cyrenaicum (Lamiaceae), collected from Tolmitha and Al-Gubba sites, respectively, in the Al-Jabal Al-Akhdar region, Libya. Chromosome number, karyotype structure, and a comprehensive set of karyomorphological parameters were investigated, including chromosome length, arm ratio, centromere index, symmetry indices, and intra- and interchromosomal asymmetry indices. The results showed that Arbutus pavarii is diploid with 2n = 2x = 26 and a karyotype formula of 4M + 16m + 6sm (4SAT), whereas Origanum cyrenaicum has 2n = 2x = 30 with a karyotype formula of 6M + 16m + 8sm (3SAT). Both species possess small-sized chromosomes, ranging from 3.09 ± 0.03 µm in Arbutus pavarii to 1.98 ± 0.02 µm in Origanum cyrenaicum. According to Stebbins’ classification, the karyotypes of both species fall into type 1A, indicating a high degree of symmetry. Satellites were detected on four chromosome pairs in Arbutus pavarii and three pairs in Origanum cyrenaicum. These findings represent the first documented karyotypes of both species and provide baseline cytogenetic data that enhance their genetic characterization and support future taxonomic, evolutionary, and conservation studies.